Implications of COVID‐19‐induced nationwide lockdown on children's behaviour in Punjab, India - Sama, Bhupinder Kaur (Child Care Health Dev, 2020)
BACKGROUND: Lockdown is one of the prevalent tools that are used to control the spread of COVID‐19 virus in India. Under the circumstances created during lockdown period, children are deprived from the social interaction and companionship; because of which, they are susceptible to psychiatric disorders. Therefore, in this study, efforts were to understand the impacts of lockdown on the mental status of the children of India and their specific causes. STUDY DESIGN: It is a questionnaire‐based study. METHODS: A web‐based questionnaire was prepared, and 400 parents from four districts of Punjab, India, namely, Ludhiana, Sahibzada Ajit Singh (SAS) Nagar, Sangrur and Ferozepur, were telephonically interviewed. Further, the information collected from the interviews was statistically analysed using Statistical Package for the Social Sciences (SPSS) software. RESULTS: Findings from this study revealed that 73.15% and 51.25% of the children were having signs of increased irritation and anger, respectively; 18.7% and 17.6% of the parents also mentioned the symptoms of depression and anxiety, respectively, among their children, which were also augmented by the changes in their diet, sleep, weight and more usage of the electronic equipment. Children (~76.3%) persistently urge to go outdoors and play with their friends; therefore, they could lag in social development. Further, observations from Pearson's correlation revealed that during lockdown, children's mental health is significantly related to the area of their house, number of children in the family, qualification of their mother and socio‐economic status of their family. CONCLUSIONS: This study made it evident that the mental health of the children residing in Punjab, India, was compromised during the lockdown period induced by the COVID‐19 pandemic. Findings of this study may also trigger the international authorities to frame the guidelines of lockdown in the interest of mental health of their native children.